(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
This research investigates the Statistical Correlation on Internal Issues of Spinning Data were collected from Primary as well as secondary sources It is a statistical research technique in decision making that is used for the selection of a limited number of tasks that produce significant overall effect. It separates the few major problems from the many possible problems. It is named after Vilfredo Pareto, a 19th-century Italian economist. It was revealed that Textile spinning sector detail of analysis performed for reducing a huge number of issues explored from textile industry of Pakistan in the era of trade liberalization. The research in this part of framework starts by conducting a survey of the textile industry of Pakistan for the collection of data through questionnaire consisted of the explored issues. The data collected through survey is then used to perform Pareto analysis and bring up the prioritized issues after reducing them by using statistical tool SPSS. Then statistical Correlation is performed on the prioritized issues reduced through Pareto analysis to find the level of relationship among these issues, so by solving one issue the other may routinely be solved.